Covalently interconnected carbon nanotubes for enhanced charge transport in pseudocapacitors. Issue 10 (14th July 2015) - Bo, Zheng; Yang, Huachao; Lv, Peng; Qian, Jiajing; Yu, Kehan; Lu, Ganhua; Wei, Wei; Yan, Jianhua; Cen, Kefa
<x xml:space="preserve">Abstract</x> In this study, a buckypaper (BP), a foil of carbon nanotubes, with covalently bonded graphene leaves is prepared as a scaffold of pseudocapacitors. The capacitive electrodes are fabricated by an in situ growth of graphene on BP followed by electrochemical deposition of MnO2. The specific capacitance, energy/power‐density, and cycle stability of the hybrid electrodes are explored by means of electrochemical impedance analysis, cyclic voltammetry measurements, and galvanostatic charge–discharge analysis. Due to the graphene interconnection between carbon nanotubes, the internal resistances of the electrodes decrease by a factor of ∼2. The MnO2/graphene/BP (MnO2/g‐BP) hybrid electrode delivers a specific capacitance as high as 1022 F g−1 at a scan rate of 5 mV s−1, based on the mass of MnO2. It exhibits excellent rate capability and cycle stability. The critical role of the covalently bonded graphene leaves in enhancing charge transport is further clarified by comparison with the electrodes without them. Therefore, this study provides a new understanding for improving the performance of metal oxide‐based electrochemical supercapacitors and can be generalized for designing next‐generation high‐performance energy‐storage devices.<inline-graphic xlink:href="ark:/27927/pgkfprqmzp" content-type="pssb201451742-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />